Acid inactivation of soybean lipoxygenase with retention of protein solubility - Cheman, Y.B.; Wei, L.S.; Nelson, A.I. (Wiley, 1989)
The use of acids to inactivate lipoxygenase in soybeans with retention of protein solubility was investigated. Inactivation of lipoxygenase was found to be irreversible when treated at pH 3.0 and below, irrespective of the acids used. The SDS‐PAGE pattern showed the disappearance of lipoxygenase bands when soybeans were acid‐treated at pH 3.0 and below. Acid treatment showed no effect on trypsin inhibitor and 60% trypsin inhibitor activity was removed by whey separation. Activity of urease was reduced to below 0.2 pH, when lipoxygenase was inactivated. PDI's of 70–76% were retained in the neutralized full‐fat soy flour after treatment with acids at about pH 3.0 while full‐fat soy material was 52–55%.